Integrating Quality Management and Male Reproductive Health in Assisted Reproduction - Fabiola C. Bento; Rita C. S. Figueira; Sandro C. Esteves (International Brazilian Journal of Urology)
ABSTRACT Quality management is essential to ensure consistent, safe, and effective outcomes in assisted reproductive technology (ART) centers. However, traditional quality assessments often overlook male infertility, which contributes to nearly half of all infertility cases. This article explores the implementation of a quality management system (QMS), specifically ISO 9001, tailored to ART centers that prioritize male reproductive health. Drawing from our experience at ANDROFERT, a male-focused fertility clinic, we demonstrate how process standardization, structured workflows, and continuous improvement strategies can optimize diagnostics, microsurgical procedures, and laboratory practices. Integrating male-specific procedures—such as varicocele repair, microdissection testicular sperm extraction (micro-TESE), and vasovasostomy—into the QMS is discussed, along with performance monitoring tools, including key performance indicators and patient satisfaction metrics. Collaboration with an academic institution is essential to support education and ensure training is aligned with quality and safety protocols. Our center's dual IVF laboratories and andrology services exemplify how advanced testing, including sperm DNA fragmentation analysis and handling of surgically retrieved sperm, are seamlessly integrated into quality pathways. By embedding male reproductive health into QMS frameworks, ART centers can improve clinical outcomes, foster interdisciplinary collaboration, and enhance patient engagement. We advocate for a multidimensional approach to quality—beyond pregnancy rates—encompassing safety, effectiveness, patient-centeredness, timeliness, efficiency, and equity. This model strengthens clinical performance and ensures sustainable, evidence-based fertility care for male patients.